Cooperative self-assembly of porphyrins with polymers possessing bioactive functions. Issue 93 (15th September 2016) - Zhao, Lizhi; Qu, Rui; Li, Ang; Ma, Rujiang; Shi, Linqi
Abstract : This review covers recent research on design strategies for the cooperative self-assembly of porphyrins with polymers and its implementation as bioactive assembly. Abstract : Natural porphyrin derivatives possess many interesting functions in biological systems. They are integrated into proteins that are essential for biological activities. Many efforts have been dedicated to mimic the microenvironment and augment the function of porphyrin/protein scaffolds. To achieve such goals, self-assembly has become one of the popular methods to construct porphyrin/protein-mimicking materials owing to its various choices of building blocks and a simple preparation process over chemical modification. Desirable characteristics of building blocks for protein mimicking include high molecular weight, predictable conformations in solution, and appropriate functional residuals. With these aims in mind, polymers are ideal candidates due to their multiple-level hierarchies derived from their chemical and spatial structures. In this review, design strategies for the cooperative self-assembly of porphyrins with polymers and the main efforts towards the implementation of porphyrin/polymer assembly for biomimetic composites with bioactive functions will be addressed.